Night skies through animals’ eyes—Quantifying night-time visual scenes and light pollution as viewed by animals - Stöckl, Anna Lisa; Foster, James Jonathan (Frontiers in Cellular Neuroscience, 2022)
A large proportion of animal species enjoy the benefits of being active at night, and have evolved the corresponding optical and neural adaptations to cope with the challenges of low light intensities. However, over the past century electric lighting has introduced direct and indirect light pollution into the full range terrestrial habitats, changing nocturnal animals’ visual worlds dramatically. To understand how these changes affect nocturnal behaviour, we here propose an animal-centred analysis method based on environmental imaging. This approach incorporates the sensitivity and acuity limits of individual species, arriving at predictions of photon catch relative to noise thresholds, contrast distributions, and the orientation cues nocturnal species can extract from visual scenes. This analysis relies on just a limited number of visual system parameters known for each species. By accounting for light-adaptation in our analysis, we are able to make more realistic predictions of the information animals can extract from nocturnal visual scenes under different levels of light pollution. With this analysis method, we aim to provide context for the interpretation of behavioural findings, and to allow researchers to generate specific hypotheses for the behaviour of nocturnal animals in observed light-polluted scenes.